Pengaruh Motivasi Kerja, Kepuasan Kerja, dan Karakteristik Individu Terhadap Komitmen Organisasi Karyawan Dinas Pendidikan dan Kebudayaan Lombok Barat - Amini, Putri; Suryatni, Mukmin (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to determine the effect of work motivation, job satisfaction, and individual characteristics on organizational commitment of employees of the West Lombok Education and Culture Office. The population of this study were 54 employees at the West Lombok Education and Culture Office. The research method used in this research is a quantitative approach. Data analysis was performed using multiple linear regression analysis. The results of this study indicate that the Work Motivation variable (X1) has a positive and significant effect on Organizational Commitment (Y), the Job Satisfaction variable (X2) has a positive and significant effect on Organizational Commitment (Y). Individual Characteristics (X3) has a positive and significant influence on Organizational Commitment (Y).